Physicochemical and functional properties of chitosan-based edible film incorporated with Sargassum pallidum polysaccharide nanoparticles. (May 2023) - Zhang, Ke; Chen, Qing; Xiao, Jie; You, Lijun; Zhu, Siming; Li, Chao; Fu, Xiong
Abstract: The blending of different matrixes and the addition of functional factors may challenge the compatibility of edible films, thus affecting their basic properties. In this study, a novel nano-polysaccharide based edible film (nSPP/CH) was developed by blending Sargassum pallidum polysaccharide nanoparticles (nSPP) with chitosan (CH). The compatibility, physicochemical, and fruit preservation properties of nSPP/CH were investigated. The results indicated that compared with native polysaccharide-based edible films, nSPP/CH exhibited thinner thickness, higher tensile strength, and greater elastic modulus. Fourier transform-infrared spectroscopy (FT-IR) and X-ray diffraction (XRD) analysis showed good compatibility between nSPP and CH through internal forces to form a stable structure. Moreover, nSPP/CH showed a good cherry preservation ability to cherries by inhibiting the respiration intensity and weight loss rate of cherries. Furthermore, the addition of thymol could improve the surface hydrophobicity and antimicrobial effect of nSPP/CH. However, the mechanical properties and water vapor permeability of nSPP/CH incorporated with thymol were decreased. Scanning electron microscope (SEM) analysis showed that the nano-polysaccharide encapsulated thymol through cavity structure was conducive to the dispersion of thymol and enhanced the compatibility of film matrixes, thus decreasing the water vapor permeability of edible film. These results suggest that nSPP/CH incorporated with thymol might be expected to be a new kind of natural green edible film to extend the shelf life of fruits. Graphical abstract: Image 1 Highlights: Polysaccharide nanoparticles (nSPP) and chitosan (CH) constructed the edible film. The nSPP could increase the mechanical and antimicrobial properties of edible film. The nSPP was beneficial to maintain the ordered structure of the edible film. The edible film incorporated with thymol could extend the shelf life of fruits.